University student´s percepctions of news of violence against woman in the media ecuadorian communication - Chóez Abad, María Lorena (2024)
The media play a fundamental role in shaping public opinion and the perception of social problems. Among university students, news of violence against women can provide clarity about how this problem is treated and how it affects the consciousness and attitudes of this young generation. The present study seeks to describe the perception of university students regarding news that addresses violence against women in the Ecuadorian media. To collect information, an online survey was applied to a sample of 338 students from the San Gregorio University of Portoviejo, Ecuador. The results obtained showed that students generally consider that the news coming from Ecuadorian media on the subject is sensationalist, and sadness is the emotion that prevails when consuming it. These are usually reported actively through digital media, aware that the information obtained is not always secure. Distrust towards the information provided by social networks is underlined.